Eroticism in the “Cold Climate” of Northern Ireland in Christina Reid’s The Belle of the Belfast City - Ojrzyńska, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2013)
Closely based on the dramatist’s personal experience, Christina Reid’s The Belle of the Belfast City offers a commentary on the life of the Protestant working class in the capital of Northern Ireland in the 1980s from a woman’s perspective. It shows the way eroticism is successfully used by the female characters as a source of emancipation as well as a means not only to secure their strong position in the private domain of the household, but also to challenge the patriarchal structures that prevail in the Irish public sphere. The analysis of the play proposed in this essay focuses on the contrast between the presentation of its male and female characters. I will demonstrate that, while the former group desperately cling to the idea of preserving the social status quo, the latter display a more progressive outlook on the social and sexual politics of the country. In particular, I will investigate how the tensions between the representatives of the two sexes reveal themselves in the corporal sphere. I will argue that, as opposed to the erotically-inhibited and physically-inarticulate male characters, the female dramatis personae take advantage of being more connected to their bodies and use their physicality in an erotic fashion to subvert the rules of the patriarchal system and its strict moral code that limits their social roles to those of respectful mothers, obedient sisters or virtuous wives.